SPOCK1 promotes tumor growth and metastasis in human prostate cancer - Chen Q; Yao YT; Xu H; Chen YB; Gu M; Cai ZK; Wang Z (Dove Medical Press, 2016)
Qi Chen,1,* Yuan-ting Yao,2,* Huan Xu,1 Yan-bo Chen,1 Meng Gu,1 Zhi-kang Cai,1 Zhong Wang1 1Department of Urology, Shanghai 9th People’s Hospital, Shanghai Jiao Tong University School of Medicine, 2Institute of Plant Physiology and Ecology, Chinese Academy of Sciences, Shanghai, People’s Republic of China *These authors contributed equally to this work Abstract: Prostate cancer is the most diagnosed noncutaneous cancer and ranks as the second leading cause of cancer-related deaths in American males. Metastasis is the primary cause of prostate cancer mortality. Survival rate is only 28% for metastatic patients, but is nearly 100% for patients with localized prostate cancers. Molecular mechanisms that underlie this malignancy remain obscure, and this study investigated the role of SPARC/osteonectin, cwcv, and kazal-like domain proteoglycan 1 (SPOCK1) in prostate cancer progression. Initially, we found that SPOCK1 expression was significantly higher in prostate cancer tissues relative to noncancerous tissues. In particular, SPOCK1 expression was also markedly high in metastatic tissues compared with nonmetastatic cancerous tissues. SPOCK1 expression knockdown by specific short hairpin RNA in PC3 cells was significantly inhibited, whereas SPOCK1 overexpression in RWPE-1 cells promoted cell viability, colony formation in vitro, and tumor growth in vivo. Moreover, the SPOCK1 knockdown in PC3 cells was associated with cell cycle arrest in G0/G1 phase, while the SPOCK1 overexpression in RWPE-1 cells induced cell cycle arrest in S phase. The SPOCK1 knockdown in PC3 cells even increased cell apoptosis. SPOCK1 modulation was also observed to affect cancerous cell proliferation and apoptotic processes in the mouse model of prostate cancer. Additionally, the SPOCK1 knockdown decreased, whereas the SPOCK1 overexpression increased cell migration and invasion abilities in vitro. Injection of SPOCK1-depleted PC3 cells significantly decreased metastatic nodules in mouse lungs. These findings suggest that SPOCK1 is a critical mediator of tumor growth and metastasis in prostate cancer. Keywords: SPOCK1, growth, metastasis, prostate cancer